PENERAPAN KEGIATAN EDUKASI PUBLIC RELATIONS NET TV DALAM MENCIPTAKAN CITIZEN JOURNALIST - Yuvita Hermayanti (MediaKom : Jurnal Ilmiah Komunikasi, 2018)
Citizen journalism has penetrated the television not only outside, but also domestically. Currently, the Indonesian television station that is intense with citizen journalism is NET TV through the NET Citizen Journalist program. NET TV has the need to fulfill the quality and quantity of citizen journalist's video that can only be met by the well-publicized and well-educated public through the integration of public relations and reporting functions. Therefore, this study aims to: Know the factors and problems that become the consideration of the implementation of public relations activities to create citizen journalist; And know the implementation of public relations education activities in creating citizen journalist. The research used case study method with qualitative approach. In-depth interviews were conducted on selected key informants chosen purposively: 4 people from NET TV and 5 people from NET Citizen Journalist. Primary data is triangulated with existing document and literature studies. The result of the research concludes that the factors that become the consideration of the implementation of educational activities are the need for awareness of NET TV in general and the Citizen Journalist NET program in particular; The need to build a NET TV lovers community; The need to increase the quantity of members and the quality of citizen journalist's video through educational activities. News Division has a need that can only be achieved by integration with Public Relations.Keywords: Public relations, education, citizen journalist